Soft skill in training of IT students - М. Гашимова; Р. Сегол; Є. Батрак; Н. Цьопа; С. Мураховський; О. Гармаш (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The article is devoted to developing soft skills for IT professionals in the process of remote learning through the introduction of team tasks using communication skills, report and presentation skills, teamwork, leadership skills, and activities under conditions of uncertainty. The experiment conducted within the framework of the study will allow us to scale the proposed methodology in the training of IT specialists in various universities. This article aims to introduce a methodology for teaching professional disciplines using the method for developing soft skills for future IT specialists. A method of teaching that helps students in a distance format, in addition to professional skills, also develops communication skills, presentation and report preparation skills, teamwork skills, emotional intelligence, and critical thinking.